Development of E-Books Oriented to Banten Culture Integrated with Challenge Based Learning to Improve Elementary School Students' Creative Thinking Skills in Science Learning - Putri, Vina Karina; Ainulhaq, Nurisa; Rahmadani, Kurniati (JTP - Jurnal Teknologi Pendidikan, 2024)
Future demands are very complex, including the ability to generate new ideas, find unique solutions, and think flexibly and elaboratively. The purpose of this study is to develop students' creative thinking skills, especially in the subjects of Natural Sciences and Social Sciences (IPAS), which are often neglected in the learning process using e-books. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data analysis was carried out using the one group pretest-posttest model. The subjects of the study were fifth grade students of SD Negeri 5 Banjarsari, Cipocok Jaya District, Serang City. The results of this study indicate that the developed E-Book is feasible and effective for use in the learning process, as evidenced by the assessment of learning design experts obtaining a score of 97.78% (very good), the assessment of content experts obtaining a score of 90.62% (very good), and the assessment of learning design and media experts obtaining a score of 97.50% (very good). The product effectiveness test also showed a significant difference between before and after using the E-Book. The results of the study concluded that the Banten Culture-oriented E-Book integrated with Challenge Based Learning (CBL) was able to improve students' creative thinking skills in science learning. The E-Book also received positive responses from both students and teachers, both in terms of content, design, and usability in the learning process. The recommendation is that this E-Book can be said to be an effective alternative learning media to improve the quality of education in elementary schools, especially in science learning.